Maternal and neonatal morbidity and mortality associated with preterm premature rupture of membranes prior to 34 week gestation at Kigali University Teaching Hospital: A retrospective and prospective study - V. Dusingizimana; M. Small; R. Teteli; S. Rulisa; U. Magriples (Rwanda Medical Journal, 2019)
BACKGROUND: Preterm premature rupture of membranes is an obstetric complication which has adverse perinatal effects and long-term morbidity and mortality. There is no published outcome data in Rwanda. OBJECTIVES: To assess maternal and neonatal outcomes at 24 to 34 weeks gestational age with preterm premature rupture of membranes (PPROM). METHODS: Retrospective chart review of patients admitted with PPROM from 2011 to 2014 in the largest teaching hospital in Rwanda. Prospective data collection was performed in the last year (2015). Overall maternal and neonatal outcomes were documented as well as a comparison of neonatal outcomes stratified into 3 gestational age groups (24 to 28 weeks, 29 to 31 weeks and 32 to 34 weeks). RESULTS: The study group was 109 patients. The mean gestational age at PPROM and delivery were 28.9 ± 2.8 weeks and 30.0 ±2.8 weeks, respectively. The majority (62.4%) delivered within one week of PPROM. Chorioamnionitis was present in 9.2%, placenta abruption in 4.6% and the cesarean delivery rate was 42.2%. The overall perinatal death rate was 38.5% and neonatal mortality rate was 30.9%. Perinatal mortality was highest in the 24 to 28 weeks gestational age group (73.5%) and in infants weighing less than 1 kg (67.9%). CONCLUSION: PPROM in our setting carries significant maternal morbidity and high neonatal mortality below 28 weeks. Parents should be thoroughly counseled about potential adverse maternal complications and poor neonatal outcome and be involved in decision-making regarding cesarean delivery and intensive neonatal care.